Revitalisasi Karakter Muda-Mudi Remaja Mesjid di Desa Sarudik Lingkungan IV dalam Meningkatkan Partisipasi Kegiatan Sosial - Indra, Indra (Innovative: Journal Of Social Science Research, 2023)
Sarudik Village is a village located in Sibolga, Central Tapanuli. Where the majority of the population in Sarudik Village, precisely in this IV environment, are people who live in the TNI dormitory area. Revitalization is a process or method and action to revive something that was previously empowered. We heard that the people there told about teenagers that the mosque in this area had been empty for 6-7 years. Therefore, the Sarudik Village community together with UIN North Sumatra Real Work Study Students re-formed the mosque youth there by embracing local youth again with the aim of increasing youth participation by directing the youth to positive activities and providing many good benefits in social life. , and reduce juvenile delinquency which is one of the problems that exist in the 4 sarudik environment. The community and parents hope that with the re-establishment of the mosque, teenagers can keep themselves busy with activities that will be held in the future for the collective benefit of Sarudik Village, Ward IV.